Proteomics of the Skin Secretion of Pulchrana glandulosa (Anura: Ranidae) (Boulenger, 1882), Langkawi Island, Kedah, Peninsular Malaysia - Ong, Dasi; Ismail, Mohd N.; Shahrudin, Shahriza (Current Proteomics, 2023)
Background: The advancement of proteomics studies leads to various benefits in research. However, in Malaysia, proteomics studies are still in their early stage. Objective: Four adult Pulchrana glandulosa individuals were collected from the stream of Temurun Waterfall for their proteomics information. Methods: These frogs’ skin secretions were collected, extracted, and analysed for their protein antimicrobial peptide compounds and biomedical potentials using liquid chromatography-mass spectrometry. Results: Forty-six proteins had been identified from the skin secretion of this species. They contained unreviewed proteins, enzymes, AMPs, receptors, regulatory, transport, hormone, and developmental proteins. In addition, 11 AMP had been identified, consisting of esculentin-2, brevinin 1, and other AMPs. Conclusion: These proteins and AMPs have a wide range of biomedical importance, such as antimicrobials, anti-tumour, anti-cancerous, anti-viral, wound healing, anti-inflammation, anti-ageing and maintaining homeostasis.
Keywords: Frog